Dentists' knowledge, attitude and practice towards silver diamine fluoride therapy in Hong Kong: a mixed-method study - Hollis Haotian Chai; Ivy Guofang Sun; Jasmine Cheuk Ying Ho; Sherry Shiqian Gao; Sherry Shiqian Gao; Edward Chin Man Lo; Chun Hung Chu (Frontiers Media S.A., 2024)
This study explored the knowledge, attitude, and practice towards silver diamine fluoride (SDF) therapy among dentists in Hong Kong. The quantitative component was an online closed-ended questionnaire survey through the Society of Preventive Dentistry of Hong Kong. The qualitative component involved individual in-depth interviews with selected dentists. Descriptive analysis was performed on the quantitative data, whereas thematic analysis was performed on the qualitative data. The quantitative study invited 173 dentists, and 86 completed the questionnaire survey (86/173; 50%). All respondents were familiar with SDF and 73 (73/86; 85%) used SDF. They agreed that SDF therapy was simple (84/86; 98%), non-invasive (84/86; 98%), timesaving (82/86; 96%), effective (81/86; 94%), and painless (79/86; 92%). However, they expressed concerns about SDF's unaesthetic staining (81/86; 94%) and used it for primary teeth (77/86; 89%). The qualitative study conducted 12 individual interviews. Dentists asserted that SDF therapy is an evidence-based practice for arresting caries, including root caries. They acknowledged SDF therapy is straightforward and cost-effective. It is particularly useful for children or people with disabilities and can be used in community service. They considered the application skills, close monitoring and maintaining good oral hygiene to be vital for the success of SDF therapy. However, they noted that black staining of the carious lesions could cause patient dissatisfaction. They suggested that a guideline is warranted for SDF use. Hong Kong dentists are aware of the indications, merits and limitations of SDF therapy. They use SDF therapy for caries control, especially for children, elderly and those with disabilities, and consider it cost-effective for community dental care.